Pengaruh Intensitas Persediaan, Leverage dan Kinerja Keuangan Terhadap Penghindaran Pajak: (Studi Empiris Perusahaan LQ-45 Yang Terdaftar di BEI Tahun 2017-2021) - Egi Dya Puji Lestari; Syafrizal (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
Tax avoidance is based on agency theory, where this theory explains that a company is a form of contract between the owner of the company (principal) and the manager (agent) of the company who takes care of use and control within the company. This study aims to determine the effect of inventory intensity, leverage and financial performance on tax avoidance in LQ-45 index companies for the 2017-2021 period. This type of research is quantitative using secondary data obtained from the Indonesia Stock Exchange (IDX) and the website of each company and the analysis technique used in this study uses multiple linear regression with the help of E-views version 10 software. This research was conducted at companies LQ-45 index. The data sampling technique uses purposive sampling, which are used as research samples are 21 companies with security for 5 years 2017-2021. The results showed that partially leverage and financial performance had no effect on tax evasion while inventory intensity had an effect on tax evasion. While simultaneously inventory intensity, leverage and financial performance have an influence on tax avoidance.